Vitamin C content and profile of ascorbate metabolism gene expression in green leaves and bleached parts of the pseudostem of leek (Allium porrum L.) F1 hybrids - M. A. Filyushin; T. M. Seredin; A. V. Shchennikova; E. Z. Kochieva (Вавиловский журнал генетики и селекции, 2025)
Leek (Allium porrum L.) is an economically important vegetable crop of the family Amaryllidaceae with a wide range of medicinal and nutritional properties, in part due to the accumulation of vitamin C (L-ascorbic acid, ascorbate). Ascorbate is an organic water-soluble compound, which performs many functions in plant cell metabolism, including as one of an effective antioxidant in plant cell responses to biotic and abiotic stress factors. Ascorbate metabolism includes biosynthesis (mainly the L-galactose pathway) and recycling (reduction of oxidized forms to ascorbate). The gene networks that determine ascorbate metabolism in leek plants are poorly understood. In this work, crosses of leek varieties/lines were carried out. Accessions of F1 hybrids were characterized for seed germination rate, ascorbate content and expression of ascorbate biosynthesis (PGI, PMI, PMM, VTC1b, GME1, GME2, VTC2, GPP, GalDH, GalLDH) and recycling (APX1, APX2, MDHAR1, MDHAR4, MDHAR5, DHAR2, GR) genes in seedlings, as well as green leaves and bleached stem parts of the adult plant. A search for correlations between the level of expression of ascorbate metabolism genes and the amount of vitamin C in leeks was also carried out. It was shown that the studied hybrids are characterized by high (89–100 %) seed germination, with the exception of the hybrid from the 74×Alligator cross (55 %). An increased level of expression of the VTC2, MDHAR1, MDHAR4 and/or MDHAR5 genes was detected in the seedlings and green leaves of nine F1 hybrids, which allowed us to consider these samples promising in terms of possible stress resistance. Four hybrids that were characterized by the lowest (33×30, 74×Alligator) and highest (81×95, 36×38) ascorbate content in seedlings were selected for a further detailed analysis of adult plants for the content of soluble sugars and ascorbate, gene expression and morphological characteristics (length, thickness and weight of the false stem). It was confirmed that green leaves of the 36×38 and 81×95 hybrids contain significantly more ascorbate than the 33×30 and 74×Alligator hybrids. In all four hybrids, the ascorbate content was significantly lower in the bleached stems than in the green leaves. Accessions 36×38 and 81×95 were also characterized by the highest amount of soluble sugars in the bleached part of the false stem used for food. In addition, the false stem formed by the 81×95 hybrid was larger and heavier than the stems of the other three hybrids. A direct dependence of ascorbate content on the transcript level of ascorbate recycling genes (APX2, MDHAR1, MDHAR4) in green leaves was revealed, which can be used in the breeding of stress-resistant leek hybrids with a high content of vitamin C.